Community Participatory Supervision in State-Owned Asset Auction Implementation in KPKNL Semarang - Saputra, Andhika Bima; Wibawa, Kadek Cahya Susila; Solechan, Solechan (Pandecta Research Law Journal, 2021)
The development of information disclosure is hand in hand with the increasing demands for community participation in government administration. Community involvement in every activity of government administration is imperative to achieve good governance, including the auction of a state-owned asset by KPKNL (State-owned Asset and Auction Service Office) Semarang Area. Community participation in the form of participatory supervision is an important element in the auction of state-owned goods because community participation, it can create a transparent and fair auction implementation. This research aimed to critically describe the urgency of community participation (participatory supervision) in the auction of state-owned goods and to analyze the implications of community involvement and non-involvement in the implementation of state-owned asset auction at the KPKNL Semarang.This research combined doctrinal legal research and non-doctrinal legal research with descriptive-analytical research specifications to be able to answer these problems. This research was also supported by a statutory approach and a qualitative approach.The results showed that the Semarang KPKNL had involved the community in the auction of the state-owned asset. The implementation of an auction that has been already online eases the public to carry out participatory supervision of the auction activities for state-owned goods. The active participation of the community encourages the realization of good governance in the auction activities of state-owned goods, especially at KPKNL Semarang. The absence of community involvement in auction implementation tends to lead to unfair and fraudulent auction practices.